Government policy commitments : opportunities to improve mental health and wellbeing : issues paper - Queensland Mental Health Commission ([Brisbane] : Queensland Mental Health Commission, 2015)
This paper summarises the key elements of the Queensland Government's policy commitments published January-March 2015 relevant to improving the mental health and wellbeing of Queenslanders. The Queensland Mental Health Commission provides a view on how each of these commitments can be implemented to support better outcomes for people with mental health and drug and alcohol problems, consistent with the Queensland Mental Health Drug and Alcohol Strategic Plan 2014-2019.
PDF caption title (viewed on February 14, 2019)
Includes bibliographical references.
Also available online (as at 25/02/19) at: https://www.qmhc.qld.gov.au/about/publications/browse/discussion-papers/government-policy-commitments-opportunities-to-improve-mental-health-and-wellbeing.
Keywords: Mental health policy -- Queensland